2011
DOI: 10.5653/cerm.2011.38.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early prepubertal exposure to bisphenol A on the onset of puberty, ovarian weights, and estrous cycle in female mice

Abstract: ObjectiveBisphenol A (BPA) is a chemical used extensively to manufacture plastics and epoxy resin liners for food and beverage cans. BPA, with properties similar to estrogen, has endocrine-disrupting effects. In the present study, we examined the effects of early prepubertal BPA exposure on the onset of puberty and reproductive parameters such as estrous cycle and reproductive organ weights in female mice.MethodsFemale mice were injected subcutaneously at postnatal day (PND) 8 with BPA (0.1, 1, 10, 100 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 54 publications
(46 reference statements)
4
85
2
1
Order By: Relevance
“…The observations that females developmentally exposed to BPA exhibited normal estrus cyclicity, ovarian and uterine weights, and were able to ovulate and produce offspring indicate that BPA-induced alterations did not interfere with the normal functioning of the HPG axis. A normal length of estrus cycle was also described in studies using ICR and CD1 mice exposed to BPA during the postnatal period (Nikaido et al 2005, Nah et al 2011 or during both gestation and lactation (Tyl et al 2008) whereas BPA exposure during the prenatal period has been shown to increase estrus cycle length (Honma et al 2002, Nikaido et al 2004). This indicates again that the time window of BPA exposure could result in different effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations that females developmentally exposed to BPA exhibited normal estrus cyclicity, ovarian and uterine weights, and were able to ovulate and produce offspring indicate that BPA-induced alterations did not interfere with the normal functioning of the HPG axis. A normal length of estrus cycle was also described in studies using ICR and CD1 mice exposed to BPA during the postnatal period (Nikaido et al 2005, Nah et al 2011 or during both gestation and lactation (Tyl et al 2008) whereas BPA exposure during the prenatal period has been shown to increase estrus cycle length (Honma et al 2002, Nikaido et al 2004). This indicates again that the time window of BPA exposure could result in different effects.…”
Section: Discussionmentioning
confidence: 99%
“…The studies investigating the effects of BPA on reproductive physiology report various effects on vaginal opening, fertility, and the estrus cycle. Exposure to BPA during prenatal or postnatal life resulted in advanced- (Honma et al 2002, Nikaido et al 2004, Nah et al 2011), delayed-(Nikaido et al 2005, or unaffected- (Howdeshell et al 1999, Tyl et al 2008 vaginal opening. Fertility was either reduced or unaltered in females exposed to BPA (Honma et al 2002, Tyl et al 2008, Cabaton et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…When treatment starts postnatally after 15 days, age at VO is not affected (Nikaido et al, 2005;Laws et al, 2000). During the age window comprised between birth and 15 days, age at VO is either not affected (Nagao et al, 1999;Adewale et al, 2009;Losa-Ward et al, 2012;Yu et al, 2010) or early (Adewale et al, 2009;Losa-Ward et al, 2012;Fernandez et al, 2009;Nah et al, 2011). A dose of 50 µg/kg causes advancement of puberty while 50 mg/kg has no effect, indicating a non-linear doseresponse relationship (Adewale et al, 2009;Losa-Ward et al, 2012).…”
Section: Female Rodentmentioning
confidence: 99%
“…The role of BPA in the canonical apoptotic pathways has been inadequately appraised and there is limited data associating its role in mitochondrial cell death of T cell lines [19] and germ cells after UV irradiation and hydroquinone treatment [20]. Moreover, epidemiological and genetic studies have shown that BPA is an environmental estrogenic compound that can exert proliferative responses and more specifically may induce hormonal--related effects [15, 20--26].…”
Section: Introductionmentioning
confidence: 99%